Acceptance and Commitment Therapy (ACT) aplication toward self acceptance and commitment to prevent the transmission of HIV/AIDS - Widjijati Widjijati; Dyah Wahyuningsih; Aris Fitriyani (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
For people living with HIV/AIDS (PLWHA), to be diagnozed AIDS is a big problem. Psychologic problem of PLWHA will lead negative behaviour toward himself such as tend to suicide since the transmission of HIV/AIDS will be cut off if it is done. Therefore, Acceptance and Commitment Therapy (ACT) can be given to PLWHA to develop aceeptance and commitment behaviour. The aim of this study is to know the impact of ACT toward PLWHA aceptance and commitment to himself and his society. It is an experimental design with non randomized pretest and posttest with control group design. Purposive sampling method is used in this study. The result shows that there was significant differences of acceptance and commitment among experimental group after receiving ACT (p=.000).